Therapeutic effect of immunoadsorption and subsequent immunoglobulin substitution in patients with dilated cardiomyopathy: Results from the observational prospective Bad Berka Registry. Issue 2 (February 2017) - Ohlow, Marc-Alexander; Brunelli, Michele; Schreiber, Matthias; Lauer, Bernward
Abstract: Background: Elimination of cardiac autoantibodies, frequently detected in patients with dilated cardiomyopathy (DCM), with immunoadsorption (IA) improves functional capacity and left ventricular (LV) function. This study aimed to prospectively address this issue in a large cohort of unselected patients. Methods: Consecutive patients undergoing IA followed by IgG substitution were included. Clinical and echocardiographic parameters were assessed at baseline (BL) and 12-month follow-up (FU). Patients were classified as IA responders when ≥2 of the following criteria were achieved: improvement in the Minnesota Living with Heart Failure Questionnaire (MLHFQ) ≥5 points, symptoms [≥1 New York Heart Association (NYHA) class], LV ejection fraction (EF) ≥10% or decrease in LV end-diastolic diameter (EDD) ≥10%, or N-terminal pro B-type natriuretic peptide (NT-pro-BNP) ≥50%. Results: 93 patients (median age 61 years, LVEF 30%, duration of symptoms 14 months, 87% in NYHA class III/IV, >90% treated with β-blocker/angiotensin-converting enzyme inhibitor) were included. When the entire cohort was analyzed, a significant improvement in MLHFQ (50 vs. 26 points), NYHA-class (median 3.0 vs. 2.0), LVEF (30% vs. 38%), LVEDD (62 vs. 59 mm), NT-pro-BNP (892 vs. 523 pg/ml) was observed at FU ( p  < 0.05 for all). 48% ( n  = 43) were classified as responders. Those were characterized by a shorter disease duration (11 vs. 22 months), larger BL LVEDD (64 vs. 60 mm), presence of >1 viral genome, and higher values of mononuclear inflammatory cells at endomyocardial biopsy. Sixteen (17.2%) patients experienced IA related complications. Conclusions: A positive response is observed in 48% of inflammatory DCM patients undergoing IA, and this translates into a significant improvement in clinical and echocardiographic parameters.